Analisis Strategi Keunggulan Bersaing Mie Gacoan Indonesia - Erwin Permana; Anwar Alif; Krisna Agung Rahmanda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of culinary tourism in Indonesia is growing rapidly. Various new types of food, new menus with new names, and new ways of serving food continue to emerge. Mie Gacoan is one of Indonesia's original culinary delights, with a variety of unique menus and names. Mie Gacoan has become one of the most popular spicy noodle products in Indonesia. This study aims to analyze the competitive advantage strategies of Mie Gacoan in Indonesia. The research was conducted using a qualitative descriptive approach. Data collection was carried out through in-depth interviews, digital observations, and documentation. The results of the study indicate that Mie Gacoan's success in attracting and retaining customers amid intense culinary business competition is driven by several key factors, including product differentiation through variations in spicy noodle menus with adjustable levels of spiciness, creative menu names, and continuous product innovation, which serve as the main attractions for consumers. Effective digital marketing strategies through social media, competitive pricing, operational efficiency in service, and strong branding also significantly contribute to Mie Gacoan's competitive advantage. To maintain its position in the market, Mie Gacoan must continue to innovate, adapt to consumer trends, and leverage customer data to enhance overall satisfaction. As a result, Mie Gacoan has successfully established a strong foundation for sustainable growth in Indonesia's culinary industry.